2007
DOI: 10.1002/uog.3859
|View full text |Cite
|
Sign up to set email alerts
|

Congenital myotonic dystrophy: prenatal ultrasound findings and pregnancy outcome

Abstract: Objective The objective of this study was to assess the maternal and prenatal ultrasound findings and outcome in pregnancies complicated by congenital myotonic dystrophy Type 1 (DM1). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 8 publications
5
44
1
5
Order By: Relevance
“…Comparing women with DM1 and DM2, pre-eclampsia was more common in DM2 (13.6% vs 9.5%), while polyhydramnios (25% vs 0.0%) and pre-term labor (31.0% vs 13.6%) were more common in DM1 (Table 2). Polyhydramnios has been specifically associated with congenital DM, which may explain why this is only reported in women with DM1 [14]. …”
Section: Resultsmentioning
confidence: 99%
“…Comparing women with DM1 and DM2, pre-eclampsia was more common in DM2 (13.6% vs 9.5%), while polyhydramnios (25% vs 0.0%) and pre-term labor (31.0% vs 13.6%) were more common in DM1 (Table 2). Polyhydramnios has been specifically associated with congenital DM, which may explain why this is only reported in women with DM1 [14]. …”
Section: Resultsmentioning
confidence: 99%
“…The prenatal manifestations of CDM may include reduced fetal movement, polyhydramnios, and ultrasound findings of talipes equinovarus or borderline ventriculomegaly. 30 At birth the cardinal features are neonatal hypotonia and feeding or respiratory difficulty. A prospective study found that 79% of infants required nasogastric feeding and 53% required transient or prolonged ventilatory support.…”
Section: Congenital Dm1 (Cdm)mentioning
confidence: 99%
“…La DM1 congénita, en especial cuando la madre está levemente afectada, se diagnostica muy raramente intraútero, a pesar de que existen alteraciones a la exploración ecográfica que podrían orientar hacia el diagnóstico (9).…”
Section: Discussionunclassified
“…La alteración ecográfica más frecuente es el polihidramnios que se observa en más del 90% de los casos entre la semana 28 y 34 (9). El polihidramnios es la consecuencia de una reducción o ausencia de la deglución fetal secundaria a una motilidad faringo-esofágica disminuida y a un enlentecimiento del vaciado gástrico (11).…”
Section: Discussionunclassified